2018
DOI: 10.1007/s00268-018-4765-9
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Wall Reconstruction Utilizing the Combination of Absorbable and Permanent Mesh in a Retromuscular Position: A Multicenter Prospective Study

Abstract: The combination of AM with very large PM in the same retromuscular position in AWR seems to be safe. The efficacy with recurrence rates below 4% in complex midline and lateral IH may be explained by the use of larger PMs that are extended and configured with the support of AMs. Reoperations on patients have confirmed the previous experimental reports on the use of the AM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 57 publications
1
23
2
Order By: Relevance
“…Only one patient developed a bulging. We did not consider a bulge as a recurrence because, even if the midline is not closed over the biological mesh, there is no interruption between the mesh and the abdominal wall layer 21,25 . Rather, we consider that for patients requiring CAWD repair, the onset of a postoperative bulging or abdominal wall weakness is an acceptable result and does not represent complete failure of the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one patient developed a bulging. We did not consider a bulge as a recurrence because, even if the midline is not closed over the biological mesh, there is no interruption between the mesh and the abdominal wall layer 21,25 . Rather, we consider that for patients requiring CAWD repair, the onset of a postoperative bulging or abdominal wall weakness is an acceptable result and does not represent complete failure of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence was defined as a fascial defect at the surgical site. Bulging was defined as a relaxing of the abdominal wall at the mesh site due to stretching of the mesh, without any interruption between the mesh and the abdominal wall layer 21,25 . Bulging was considered in the SSO group and was not considered as a recurrence.…”
Section: Study Outcomesmentioning
confidence: 99%
“…1). Of these, three (25%) examined bioabsorbable mesh for prophylaxis [14][15][16] and nine (75%) reported repair after incisional hernia/abdominal wall reconstruction [17][18][19][20][21][22][23][24][25]. Studies for prophylaxis included a total of 201 patients with a median follow-up of 11 months (range 9-24 months) and those for repair included 1086 patients with a median follow-up of 23 months (range 1-26 months).…”
Section: Resultsmentioning
confidence: 99%
“…Gore-BioA® (WL Gore, Arizona, USA) was the most used mesh for prophylaxis of the abdominal wall used in two studies [15,16], followed by TIGR® (Novus Scientific, Uppsala, Sweden) in one study [14]. In papers reporting bioabsorbable mesh for repair only, Phasix™ (BD Bard, Rhode Island, USA) [18,19,24,25] was the most commonly reported followed by Gore-BioA® (n = 3) [20,22,23]. One study [21] reported use of Phasix™, TIGR®, Gore-BioA®, and another study [17] did not report type of bioabsorbable mesh used.…”
Section: Resultsmentioning
confidence: 99%
“…2020 Oct;7(10): [3348][3349][3350][3351][3352][3353] International Surgery Journal | October 2020 | Vol 7 | Issue 10 Page 3349 limitation in medialization of rectus muscles causing large surfaces of mesh to be located under the skin flaps, hence resulting in surgical site events (SSE) and recurrences. [2][3][4] AWR has been recently revolutionized by minimally invasive reconstructive techniques, exponential growth of bioprosthetic have revolutionized. And, introduction of components separation has facilitated closure of both posterior and anterior layers in wide defects, and location of large meshes in a completely preperitoneal space.…”
Section: Introductionmentioning
confidence: 99%